Comparison of electrogenic glucose transport processes and permeability between proximal and distal jejunum of laying hens. Issue 3 (4th May 2017) - Metzler-Zebeli, B. U.; Hollmann, M.; Aschenbach, J. R.; Zebeli, Q.
ABSTRACT: 1. The current objective was to assess (1) differences in mucosal transepithelial short-circuit current (Isc ) and tissue conductance (GT ), (2) the effect of a glucose stimulus and (3) epithelial paracellular permeability in the proximal and distal jejunum of laying hens. 2. Proximal and distal jejunal segments used in the Ussing chambers were collected at 9 ± 0.5 and 73 ± 3.4% (SEM) of jejunal length, respectively. The proximal jejunal mucosa showed a small negative Isc (−1.3 µA/cm 2 ), whereas the distal jejunum had a higher Isc (32.9 µA/cm 2 ). Similarly, GT was 2.5-fold greater in the distal compared to the proximal jejunum. 3. Increased paracellular permeability in the distal jejunum was displayed as demonstrated by a 5-fold higher mucosal to serosal flux of fluorescein isothiocyanate and horseradish peroxidase, representing molecules of low and high molecular weight, respectively. 4. Addition of glucose to the mucosal side (5 mmol/l, final concentration in the chamber) to stimulate an absorptive effect caused 3-fold greater GT in the distal compared to the proximal jejunum. 5. In conclusion, the present results supported site-specific electrogenic transport processes for the jejunal mucosa of laying hens. Therefore, precise description of the jejunal site may contribute to an improved comparability of electrophysiological data.